Men as Allies Against Sexism: The Positive Effects of a Suggestion of Sexism by Male (vs. Female) Sources. (6th June 2014) - Cihangir, Sezgin; Barreto, Manuela; Ellemers, Naomi
Sexism is often expressed in subtle and ambiguous ways, causing targets to doubt their own capabilities or to show stereotype-confirming behavior. This research examines whether the self-confidence and stereotype (dis-)confirming behavior of targets of sexism can be bolstered when other male versus female sources suggest that sexism may have played a role. Both Study 1 ( N = 78) and Study 2 ( N = 90) show that a suggestion of sexism has more beneficial effects when it is made by male sources than when it is made by female sources. When males suggested that sexism had taken place, targets reported more self-confidence (less self-handicapping and higher personal performance state self-esteem) and showed less stereotype confirmation (less self-stereotyping and better task performance) than when sexism was suggested by a female source. Study 2 additionally revealed that targets are more likely to file a complaint when men suggest that sexism took place than when this same suggestion was made by women. These results indicate that men can constitute important allies against sexism if they speak out when sexist treatment takes place.